2007
DOI: 10.1111/j.1365-2435.2007.01257.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of predation behaviour as a putative driving force for parasite life‐cycle dynamics: the case of urban foxes andEchinococcus multilocularistapeworm

Abstract: Summary1. Parasite transmission frequently depends on an intermediate host species being subject to predation by a definitive host. We hypothesized that the population dynamics of this type of parasite would be affected by plasticity of the predation behaviour of the final host. The zoonotic tapeworm Echinococcus multilocularisLeuckart is transmitted to foxes ( Vulpes vulpes L.) by predation on infected rodents. One possible mechanism underlying the significant decrease in the prevalence of E. multilocularis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
100
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(108 citation statements)
references
References 34 publications
(51 reference statements)
6
100
1
1
Order By: Relevance
“…The same trend was observed in Switzerland: Zürich (Hegglin et al, 2007;Hofer et al, 2000) and Geneva (Fischer et al, 2005). The first report of an urban cycle for E. multilocularis concerned the city of Zürich.…”
Section: Gradient Of Infection and Urbanisation Levelsupporting
confidence: 67%
See 3 more Smart Citations
“…The same trend was observed in Switzerland: Zürich (Hegglin et al, 2007;Hofer et al, 2000) and Geneva (Fischer et al, 2005). The first report of an urban cycle for E. multilocularis concerned the city of Zürich.…”
Section: Gradient Of Infection and Urbanisation Levelsupporting
confidence: 67%
“…The analysis of the effect of urbanisation level, year, season, age class and sex have shown that urbanisation only explained fox infection. Other studies have revealed a seasonal prevalence in an urban area with higher rate in winter for young males (Hofer et al, 2000) and more pronounced variation along the urbanisation gradient in juveniles foxes than in adult foxes (Hegglin et al, 2007). In our study urban positive cases were juveniles males.…”
Section: Gradient Of Infection and Urbanisation Levelsupporting
confidence: 51%
See 2 more Smart Citations
“…The infection pressures reported for E. multilocularis assume that infection pressure is constant throughout the year which is unlikely. In Switzerland for example, differences in prevalences have been suggested between foxes sampled in the winter and the summer (Hofer et al, 2000;Stieger et al, 2002;Hegglin et al, 2007). Studies are being undertaken to resolve the issues of seasonal transmission in Kyrgyzstan.…”
Section: Discussionmentioning
confidence: 99%